THE MACHINE AND THE READER: CONTRASTING PERSPECTIVES ON LIFE IS A CARAVANSERAI - Yaşar Ali Sarkiler (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This study aims to examine Emine Sevgi Özdamar’s work Life is a Caravanserai through a comparative method using digital and traditional reading practices. In the study, the structural analysis performed by a Large Language Model (Gemini 3 Pro) and the aesthetic/critical reading performed by a Human are compared within the axis of seven basic concepts in the text (love, respect, justice, solidarity, freedom, empathy, division of labor). As a result of the analyses, it was observed that the Gemini 3 Pro model analyzed the text mainly in the light of concrete historical and social data. This approach based the characters’ experiences on factual cause-and-effect relationships such as poverty, state authority, migration, and gender roles. In contrast, the Human-oriented reading focused on the work’s linguistic atmosphere, metaphorical structure, and psychological depth. In this perspective, the same concepts were examined through dream imagery, childhood perception, and mental defense mechanisms. For instance, while the concept of "freedom" embodied a physical displacement (migration to Germany) in the AI analysis, it was characterized as a mental escape from harsh reality and a search for an inner refuge in the human analysis. This paper argues that the data-driven analysis revealing the sociological dimension of the work and the human interpretation decoding its emotional and imagistic layers are complementary to each other. It is concluded that synthesizing the approach examining material conditions with the approach analyzing the inner world of the characters is necessary to fully grasp the work.